The Role of Local Government in Development Planning: A Study on the Sukabumi District Government - Anwar; Dina Lesmana (Institute of Computer Science (IOCS), 2022)
The realization of a prosperous society is the goal of living in a state, where the role of the State/Government becomes very vital and integral in realizing these ideals, because the government acts as a facilitator as well as a regulator. The Central Government to District/City Regional Governments have the responsibility to mobilize all components of community empowerment, one of which is through tourism development. The guidance and development of tourism is carried out with due regard to the preservation of national culture and personality. For this reason, it is necessary to take more directed steps and arrangements based on integrated policies, including in the fields of promotion, provision of facilities and quality, and smooth service. This study aims to determine the strategy carried out by the local government of Sukabumi Regency in order to develop Ciletuh Geopark ecotourism and the results of this study explain that the Sukabumi Regency local government's strategy in developing Ciletuh geopark ecotourism in Sukabumi refers to the Governor's Regulation on plans that contain tourism development policies. West Java and the Regional Regulation of Sukabumi Regency Number 13 of 2009 it is stated that the priority of tourism development is more directed at the creation of superior tourist destinations that can prosper the lives of the wider community, by setting a more strategic regional vision and mission so that in the future the development of tourism in the Sukabumi Regency is expected to be able to improve foreign exchange earnings, as well as expanding employment opportunities, and encouraging other supporting industrial activities.